First-trimester irisin and fetuin-A concentration in predicting macrosomia. (2nd September 2019) - Zbucka-Kretowska, Monika; Kuzmicki, Mariusz; Telejko, Beata; Goscik, Joanna; Ciborowski, Michal; Lipinska, Danuta; Hryniewicka, Justyna; Citko, Anna; Lawicki, Slawomir; Wolczynski, Slawomir
Abstract: Objective: We investigated the diagnostic value of first-trimester adipokines and placental markers in predicting macrosomia. Methods: Out of 328 women recruited during the prenatal diagnosis between 11th and 13th week of pregnancy and subjected to follow up until delivery, we selected 26 women who gave birth to macrosomic babies and 34 women who gave birth to normal weight neonates for the evaluation of first trimester serum levels of pregnancy associated plasma protein-A, free β-human chorionic gonadotropin, placental growth factor (PIGF), and selected adipokines. Results: The mothers of macrosomic infants had higher PIGF ( p  = .049) and irisin concentrations ( p  = .00003), and lower fetuin-A levels ( p  = .0002) than had the mothers of normal weight babies. Newborn's weight correlated positively with maternal irisin (R = 0.454, p  = .0003) and negatively with fetuin-A concentrations (R = −0.497, p  = .00005). Multiple regression analysis showed that only serum irisin concentration was a significant predictor of birth weight (β = 0.329, p  = .03), explaining 14% of its variability. The sensitivity and the specificity of irisin concentration in predicting macrosomia were 0.769 and 0.794, respectively (AUC = 0.818 [95%CI: 0.708–0.928], p  = .00001) with a proposed cut-off value of 1725.4 ng/ml. Conclusions: Our results suggest that mother's irisin may be an early biomarker of macrosomia.